Modelos mentais de estudantes dos ensinos fundamental e médio sobre o dia e a noite a partir de um referencial na superfície da Terra e fora dela - Gomide, Hanny Angeles (2017)
This research tried to point out subsidies for the elaboration of proposals focused on Astronomy Education, related to the teaching of the day / night theme, based on the mental models of Elementary and Middle School students, when they explain this phenomenon according to a referential based on the surface of the Earth And out of it. The research aimed to interpret, through the mental models constructed by the students, their explanations on the day / night phenomenon, contemplating: how this cycle occurs, which stars are involved and how they organize in the sky. It was also questioned how the students explain this phenomenon, based on a reference in the surface of the Earth and outside it. Thus, we try to answer: What mental models are presented by students of Elementary and Middle Schooling when explaining the day / night when taken from the surface of the Earth and outside it? In addition, we seek to know if these same students transit in their explanations on the same phenomenon, when they analyze it according to different references. Fifty-eight students participated in this study: 18 of the 5th year, which corresponds to the end of Elementary School I, 20 of the 9th year, being the end of elementary education II and 20 of the 3rd year of High School, corresponding to the final years of each stage of Education Basic. The study was based on a qualitative approach, with the survey of authors who used the mental models on day and night in work with students, together with the results obtained with the students participating in this research. We take the following data sources: oral - use of semi-structured interview; Graphical - records made by the students and, imagery- simulation with physical models. The data were presented according to three axes of analysis, corresponding to the levels of teaching researched. For each axis, four categories were listed, which are: 1- Models of Earth, Sun and other stars revealed by students; 2- Movements described by the stars; 3- Explanations of the students about the alternation of the day / night cycle seen from the surface of the Earth; 4- Explanations of the students about the alternation of the day / night cycle seen from outside the Earth. Each category was analyzed according to the three sources used. Thus, based on the explanations and analysis of the data of the students, four types of mental models were denominated, denominated of: introductory - explanations based on the immediate observation of the sky; Intermediary-present knowledge that aggregates everyday experience, with scientists, not being totally coherent and plausible; Integrated - guided by knowledge with a certain scientificity; Inconsistent-are explanations pulverized and inconstant, without plausible reasoning. In general, the results indicate that the largest number of models raised by the students is the intermediate and there was no presence of the integrated model. The majority of students presented explanations about the day / night phenomenon, which pass between the different references adopted, but these are not permeated by arguments coherent with each locality of analysis. In this direction, we point out proposals to be implemented in several aspects, such as articulated and coherent work in the classroom and the use of school space for the observation of the sky.